A question of aggregation A comparative study of objective function creation methods applied to missile defense for helicopters - djurfeldt, hanna (My University, 2014)
This report describes an investigation done about method one can use when creating a target function for optimization and the e ects of those choices. Three simple and four advanced target function creation methods are described in detail and the results from optimizing with these target functions are analyzed. Lastly suggestions into possible continuations of this investigation is made.
Keywords: Grundläggande vetenskaper; Energi; Annan teknik; Hållbar utveckling; Innovation och entreprenörskap (nyttiggörande); Basic Sciences; Energy; Other Engineering and Technologies; Sustainable Development; Innovation & Entrepreneurship